2016
DOI: 10.1016/j.ydbio.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Organogenesis of adult lung in a dish: Differentiation, disease and therapy

Abstract: The remarkable regenerative capacity of the lung suggests that stem cells could be of therapeutic importance in diverse lung diseases; however, the successful exploitation of lung stem cell biology has long been hampered by our inability to maintain and expand adult lung stem cells while retaining their multi-lineage potential in vitro. Recently, advances in our understanding of stem cell niches and the role of key signalling modulators in controlling stem cell maintenance and differentiation have fuelled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 76 publications
1
24
0
1
Order By: Relevance
“…4b). Immunofluorescence (IF) showed that the organoids were composed of basal cells expressing p63 in the outer cell layer 25,28 , as well as mucin-secreting cells (goblet cells) expressing MUC1 28 and ciliated cells expressing acetylated-tubulin and Arl13b in the luminal cell layer 25,28 (Fig. 4c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b). Immunofluorescence (IF) showed that the organoids were composed of basal cells expressing p63 in the outer cell layer 25,28 , as well as mucin-secreting cells (goblet cells) expressing MUC1 28 and ciliated cells expressing acetylated-tubulin and Arl13b in the luminal cell layer 25,28 (Fig. 4c).…”
Section: Resultsmentioning
confidence: 99%
“…Organoid models for both tracheobronchial and alveolar tissue have been developed from adult stem cells or pluripotent stem cells 2527 and shown to recapitulate the epithelial organisation of these two distinct tissue types in vitro 14,26,28 . As personalised models for lung cancer, in vitro tissue culture 29 or tumour spheroid culture 10,30 using a 3D culture system has been studied to predict response to anticancer therapy, but have limited growth or recapitulation of original tumour architecture 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Innovative live cell labeling combined with the use of viral transduction systems for gene editing will allow for mechanistic analysis of such lung tissue models in the future . The rapid development of stem cell based technologies; decellularization procedures and tissue printing make the building of human‐lung related tissue pieces for use in basic science more realistic within the next years.…”
Section: Further Developments – Where Should We Go From Here?mentioning
confidence: 99%
“…Cells in 2D culture are not surrounded by ECM and therefore are different from the structure of an in vivo cell system, as they cannot: migrate, polarize, differentiate in response to [9]- [12]. Despite their proven value in biomedical research, 2D models cannot support differentiated and cell-specific functions in tissues or accurately predict in vivo tissue functions and drug and biological modulator activities [13]- [16]. These limitations have led to a growing interest in the development of more complex models, such as those that incorporate multiple cell types or involve cell modeling, and in three-dimensional (3D) models, which better represent the spatial and chemical complexity of living tissues [17]- [19].…”
Section: Introductionmentioning
confidence: 99%